ANALISIS PENGGUNAAN SINGKATAN MELALUI JEJARING SOSIAL WHATS APPLICATION (WA) PADA GRUP KAZAKHSTAN - Audhini Saffanah; Rochmat Tri Sudrajat; Eli Syarifah Aeni (IKIP Siliwangi, 2020)
The use of good language is very necessary in communicating. In addition to the use of language, the communication process requires active, creative, productive, and appreciative appreciation of language skills. One of them is through the use of abbreviations. Along with the times, the use of abbreviations was often used by Whats App users. Of course, the use of abbreviations must pay attention to grammar in order to be understood, and accepted by the reader. The purpose of this study, namely 1) explain the forms of abbreviations through Whats App social networks, 2) find out the factors that cause the use of abbreviations through Whats App messages. The research method used is descriptive qualitative method to obtain original data. The data collected is a conversation between a Kazakh group who is an alumni of SMK Fithrah Insani. The population in this study was 31 Kazakh group participants. The study sample was 10 Kazakh group participants. The data was obtained through interviews and observations. Based on the results of the study, it can be concluded that the researcher found ten Kazakhstan group participants who used abbreviations by keeping each syllable in their sentences. Factors for using abbreviations, namely 1) saving time in typing messages, 2) following a growing trend, 3) Writing abbreviations is usually only for friends, 4) Users feel that using abbreviations will not feel stiff to fellow friends in communicating.